Meaning in Structure and the Structure of Meaning in La Modification and La Route des Flandres - Katherine Passias (Studies in 20th & 21st Century Literature, 1985)
Stream of consciousness novels employ a variety of narrative techniques to depict the flow of consciousness. This article examines narrative structures underlying the subjective frame created by a sole character/narrator in two French New Novels, Michel Butor's La Modification and Claude Simon's La Route des Flandres. There is a dynamic relationship between form and content. Conventional narrative syntax in Butor's work reflects the evaluative and associative processes of the mind attempting to resolve an emotional conflict. In Simon's work, narrative structures mirror the complex embedding of four main fables as the narrative process attempts to depict the uncontrolled thought patterns evoked in a half-asleep state. The rational and the illusory functions of the mental process that differentiate these novels are reflected not only in the narrative structures but also in their global form, theme and conception of the role of language in a work of art.
Keywords: narrative structure; frame; narrator; Michel Butor; La Modification; Claude Simon; La Route des Flandres; evaluative; associative; processes; mirror; fables; half-asleep; state; rational; illusory; language; art